Application of Halogen-Bonding Catalysis for Markovnikov-Type Hydrothiolation of Alkenes - Zhang, Xue; Liang, Nuoyu; Li, Ruining; Sun, Zhankui (Synlett, 2023)
Carbon–sulfur bond-formation reactions are applied widely in organic synthesis and chemical biology. Hydrothiolation of alkenes provides a direct way to build carbon–sulfur bonds. Most known methods proceed via radical processes and result in anti-Markovnikov-type products. Herein, we demonstrate that I2 catalyzes the hydrothiolation of alkenes and provides Markovnikov-type products in good to excellent yields. Titration studies revealed that thiol was activated by I2 through halogen bonding. This metal-free reaction has advantages such as green and mild conditions, high functionality tolerance, broad substrate scope, and atom economy. Its application was further demonstrated in peptide syntheses.
Keywords: thiols; halogen bonding; hydrothiolation; Markovnikov reaction; alkenes; addition